Effects of Glucono-δ-Lactone and Transglutaminase on the Physicochemical and Textural Properties of Plant-Based Meat Patty - Haesanna Kim; Mi-Yeon Lee; Jiseon Lee; Yeon-Ji Jo; Mi-Jung Choi (Foods, 2022)
Due to growing interest in health and sustainability, the demand for replacing animal-based ingredients with more sustainable alternatives has increased. Many studies have been conducted on plant-based meat, but only a few have investigated the effect of adding a suitable binder to plant-based meat to enhance meat texture. Thus, this study investigated the effects of the addition of transglutaminase (TG) and glucono-δ-lactone (GdL) on the physicochemical, textural, and sensory characteristics of plant-based ground meat products. The addition of a high quantity of GdL(G10T0) had an effect on the decrease in lightness (L* 58.98) and the increase in redness (a* 3.62). TG and GdL also decreased in terms of cooking loss (CL) and water holding capacity (WHC) of PBMPs. G5T5 showed the lowest CL (3.8%), while G3T7 showed the lowest WHC (86.02%). The mechanical properties also confirmed that G3T7-added patties have significantly high hardness (25.49 N), springiness (3.7 mm), gumminess (15.99 N), and chewiness (57.76 mJ). The improved textural properties can compensate for the chewability of PBMPs. Although the overall preference for improved hardness was not high compared to the control in the sensory test, these results provide a new direction for improving the textural properties of plant-based meat by using binders and forming fibrous structures.